Learning Islamic Religious Education and Character with the Discovery Learning Model to Improve Students' Critical Thinking Ability - Qurrotu A’yunin; Irma Soraya; Asep Saepul Hamdani (UIN Sunan Gunung Djati Bandung, 2022)
The ability to think critically is one of the skills that must be possessed by students in the 21st century to face the development of all aspects of life. This study aims to analyze the discovery learning learning model to improve the critical thinking skills of fourth grade students on PAI and BP subjects at SDN Banyusokah 2 Sampang Regency. The type of research used is Classroom Action Research (CAR) which includes cycle I and cycle 2. The instruments used are observation sheets and critical thinking written tests. The results showed that there was an increase in students' critical thinking skills from cycle I to cycle with a percentage of 72% to 86%.